REPRESENTATION OF IDEOLOGY IN INDONESIAN PROGRAMS LAWYER CLUB (ILC) tvOne BASED ON MICROSTRUCTURE ANALYSIS OF CRITICAL DISCOURSE MODEL TEUN A. VAN DIJK: REPRESENTASI IDEOLOGI DALAM PROGRAM INDONESIA LAWYER CLUB (ILC) tvOne BERDASARKAN STRUKTUR MIKRO ANALISIS WACANA KRITIS MODEL TEUN A. VAN DIJK - Muhammad Kasir (Jurnal Kata, 2021)
The problem formulation in this study is how is the Representation of Ideology in tvOne's Indonesia Lawyer Club (ILC) Program based on the microstructure of critical discourse analysis model Teun A. van Dijk?. The purpose of this research is to describe the Representation of Ideology in the Program Indonesia Lawyer Club (ILC) tvOne based on the microstructure of the analysis of the discourse ktiris Model Teun A. van Dijk. The method used is descriptive research method with qualitative approach. This research data is the speeches of speakers in the talk show Program Indonesia Lawyer Club episode 03 December 2019 with the theme "Back and Forth FPI Permit". This study used the technique of transcribing ILC video talk shows and grouping ILC talk show transcription data into the structure/level of van Dijk's microstructure discourse. The structure or elements presented by Van Dijk to be analyzed are about thematic (theme or topic), schematic (schematic or plot), semantics (background, details, intent, preconceivedence, nominations), syntax (sentence form, cohesion, pronouns), stilistic (lexicon) and rhetoric (graphics, metaphors, expressions). The results showed that each structure/element is an ideological representation of semantics involving the background used in each segment of the ILC show. This can be revealed in more detail through each question thrown by the host, Karni Ilyas. These sentences use conjunctions that connect the causes spoken by the sources and can also be marked by the use of pronouns. A stilistic ideological representation of Islamophobia that states that there are people or groups of people who are very anti with Islam, they want to divide the Indonesian nation. The rhetorical ideological representation in each segment can be seen from the expressions of the speakers who are sometimes relaxed, focused and there are also two tensions between the speakers. In representing its ideology, speakers use distinctive language styles, such as the metaphorical style "smoke grenade", "islamophobia", and "belling/selebre case".